Morphometric characterization of Black Bengal Goat under farming condition in Bangladesh - Jalil, MA; Choudhury, MP; Kabir, MM; Habib, MA (Asian Journal of Medical and Biological Research, 2018)
The study was undertaken to characterize of Black Bengal Goat (BBG) under farming condition. Data on the different parameters were collected during July 2006 to June 2013 at BLRI goat research farm. A total of 299 animals of different ages from birth to 36 months of both sexes were included. All type of measurements were taken when goats standing freely. All measurements were taken in metric unit. Data were analyzed by SPSS version 17.0 statistical computer program. In BLRI goat herd, four different types of coat color were observed in BBG i.e. Black, Black and white, Black and brown and completely white. Body length is higher in males than that of females for all generation and age group. Male goats had higher heart girth than that of female goats irrespective of age and generations. Average adult (>24 months age) body weight of male and female goats as 29.9±1.76 and 23.6±0.81 kg, respectively. Wither height was higher in adult males than females for same age. Left and right horn length in both sexes ranged from 3.6 to 13.2 cm. Female goats had higher ear length than male goats. Tail length of Black Bengal goats ranged from 8.0±0.52 to 11.1±0.43 cm and tail breadth ranged from 2.1±0.10 to 3.6±0.43 cm for different age and sex group. Average male foreleg length in >24 months of age possessed higher than that of female. Average udder length and breadth of BBGs were 7.5±0.24, 11.7±0.44 and 14.3±0.46 and 5.9±0.16, 7.4±0.28 and 7.8±0.23 cm, respectively for age groups 6-12, 12-24 and >24 months of age. The average testis length and breadth in adult males were 9.1±0.18, 7.5±0.48 and 9.8±0.49 and 6.8±0.13, 5.2±0.27 and 6.3±0.32, cm respectively for 6-12, 12-24 and >24 months of ages groups. Asian J. Med. Biol. Res. March 2018, 4(1): 95-104